The Use of Augmented Reality as an Interactive Learning Tool to Address Students’ Learning Difficulties - Nina Fadilah; Sisi Rosida; Yahya Maulana (The Future of Education Journal, 2026)
Applied mathematics learning continues to face significant challenges because many mathematical concepts are abstract, symbolic, and require strong visualization skills. The urgency of this issue is reinforced by the 2022 PISA results, which indicate that only 18% of Indonesian students achieved the minimum proficiency level in mathematics, far below the OECD average of 69%. This condition highlights the need for innovative learning approaches capable of connecting mathematical concepts with more concrete, interactive, and contextual learning experiences. This article aims to describe innovations in applied mathematics learning through the utilization of Augmented Reality (AR) technology. Augmented Reality enables students to observe mathematical objects in three-dimensional visual forms, explore concepts directly, and connect abstract representations with real-world phenomena. Numerous studies have demonstrated that the use of Augmented Reality in mathematics education can improve conceptual understanding by approximately 25.6%, while classroom action research employing AR-assisted instruction has reported an increase in average student achievement scores from 44.57 to 87.35. These findings indicate that AR possesses significant pedagogical potential in supporting more active, visual, and meaningful mathematics learning experiences. Therefore, the integration of Augmented Reality into applied mathematics learning can serve as an innovative alternative for improving instructional quality, strengthening conceptual understanding, and fostering students’ critical thinking skills. This innovation is also highly relevant to the demands of 21st-century education, which emphasize technological literacy, problem-solving abilities, and higher-order thinking skills.